Association of very Low-density Lipoprotein Cholesterol with All-cause and Cardiovascular Mortality in Peritoneal Dialysis - Xishao Xie; Xiaohui Zhang; Shilong Xiang; Xingqun Yan; Haojie Huang; Yuanshi Tian; Zhangfei Shou; Jianghua Chen (Karger Publishers, 2017)
Background/Aims: Cardiovascular disease (CVD) is the leading cause of death in dialysis patients. Little is known about the relationship between very low-density lipoprotein cholesterol (VLDL-C) and cardiovascular mortality in these patients. Methods: A total of 1324 incident patients who began continuous ambulatory peritoneal dialysis (CAPD) therapy at our hospital between January 1, 2005, and September 30, 2014, with baseline serum VLDL-C values were investigated. The associations of the VLDL-C levels with all-cause and cardiovascular mortality were assessed. Results: The mean age of the cohort was 50.2 ± 14.8 years, and the mean VLDL-C level was 33.6 ± 18.0 mg/dl. One hundred sixty-five (12.5%) patients died during the study period. Multivariable models revealed that the high VLDL-C group was associated with significantly higher all-cause (HR, 2.08, 95% CI, 1.13 to 3.29, P = 0.002) and cardiovascular mortality (HR, 1.92, 95% CI, 1.18 to 4.29, P = 0.013) compared with the low VLDL-C group even after adjusting for various covariates. Using the VLDL-C level as a continuous variable, the hazard ratios (HRs) of all-cause and cardiovascular mortality associated with a 10-mg/dl increase in VLDL-C level were 1.12 (95% CI, 1.02 to 1.26, P = 0.025) and 1.11 (95% CI, 1.02 to 1.22, P = 0.029), respectively. VLDL-C was associated more strongly to all-cause (e.g., Akaike information criteria of 1990.205 vs. 1994.451) and cardiovascular (e.g., Akaike information criteria of 984.146 vs. 985.634) mortality than triglyceride (TG) levels. Conclusions: An elevated VLDL-C level is an independent risk factor for all-cause and cardiovascular mortality in peritoneal dialysis (PD) patients.